Pengaruh Leadership Style Terhadap Job Satisfaction dan Financial Performance Pada Sektor Perbankan Di Surabaya - Christopher Adrian Lukito; yulius Jogi Christiawan (Business Accounting Review, 2016)
This study aimed to examine the affect of leaadership style to financial performance and job satisfaction in banking sector in Surabaya. The sample used in this study was 30 banking corporates in Surabaya listed in Bursa Efek Indonesia (BEI) with 150 employees and Return of Asset (ROA) in 2015. Partial Least Square method was used to analys the data. The result of this study showed that leadership style had positive and significant affect on job satisfaction, job satisfaction had positive and significant affect on financial performance, and leadership style had positive and significant affect on financial performance.